Evaluating A School–Home Screen-Time Policy: A Mixed-Methods Pilot Study at TK Islam Alam Nusantara, Indonesia - Siti Rahma Assyarifa; Hasan Sazali (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
Young children’s screen use occurs primarily within the home, limiting the ability of schools to align family media routines with classroom learning demands. This pilot study evaluated the feasibility of an initial school-developed Standard Operating Procedure (SOP) for screen-time management at TK Islam Alam Nusantara in Bandung, Indonesia. The study employed an embedded mixed-methods design in which qualitative policy evaluation constituted the primary component, supported by a 30-day single-group pretest–posttest assessment. Five children with relatively high screen exposure and marked classroom attention or behavioral difficulties were selected through purposive extreme-case sampling. Data were collected through parent and teacher questionnaires, post-simulation interviews, structured classroom observations, and textual analysis of the initial SOP. The findings identified three operational weaknesses in the initial policy: ambiguous instructions, limited practical support for families, and the absence of a follow-up consultation mechanism. Three patterns of parental adaptation also emerged: substantive compliance, formal compliance, and regulatory evasion. Consistent implementation was associated with greater apparent improvements in children’s attentional focus, emotional regulation, and contextual verbal communication, whereas limited family time, commuting pressures, and parenting fatigue constrained implementation. Based on these findings, the initial SOP was reconstructed into a more supportive school–home partnership guideline incorporating explicit procedures, school-supported content curation, accessible home-based activities, and psychological consultation. Because the study involved only five children, lasted 30 days, and lacked a comparison group, the behavioral findings should be interpreted as preliminary indications rather than evidence of causal effectiveness. The study demonstrates that school-based screen-time guidance is more feasible when it combines operational clarity, practical assistance, and sensitivity to diverse family conditions.